Photocatalytic degradation of tetracycline hydrochloride over rugby-like β-Ga2O3 with a 3D hierarchically assembled porous structure for environmental remediation. Issue 10 (7th May 2020) - Zeng, Lingxing; Wang, Jiaqi; Qian, Qingrong; Chen, Qinghua; Liu, Xin-Ping; Luo, Yongjin; Xue, Hun; Li, Zhaohui
Abstract : A novel rugby ball-like β-Ga2 O3 photocatalyst with a 3D hierarchically assembled porous structure was constructed via a facile precipitation–calcination method. The as-synthesized Ga2 O3 exhibits a high photocatalytic efficiency compared to commercial Ga2 O3 and Degussa P25. Abstract : A novel rugby-like β-Ga2 O3 photocatalyst with a 3D hierarchically assembled porous structure was successfully constructed through a facile precipitation–calcination method. The synthesized Ga2 O3 materials were used for the photocatalytic degradation of tetracycline hydrochloride (TC·HCl) and the effects of calcination temperature on photocatalytic activity were discussed. The conversion of TC·HCl over Ga2 O3 -900 was 99.0% after 25 min of UV-light irradiation, which was higher than those of commercial Ga2 O3 (71.2%) and P25 (82.9%). The best photocatalytic activity of Ga2 O3 -900 could be attributed to its large specific surface area, intrinsic electronic properties and stable 3D hierarchically assembled porous structure. Based on the liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QTOF-MS) analysis, the photocatalytic mechanism of Ga2 O3 and feasible degradation pathway of TC·HCl were proposed. We believe that the present study can exploit an effective avenue to design photocatalysts with 3D hierarchical porous structures to meet ever-increasing environmental remediation requirements.